Diagnostic Accuracy of Fluoroscopy, Radiography, and Computed Tomography in Detecting Cement Leakage in Kyphoplasty - Palm, Hans-Georg; Riesner, Hans-Joachim; Lang, Patricia; Haentzsch, Madlen; Friemert, Benedikt; Hackenbroch, Carsten (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Purpose Cement leakage is a typical complication of kyphoplasty for vertebral fractures. It is unclear if cement application intraoperatively can be improved by using other techniques of visualization and which kind of postoperative imaging should be recommended to detect cement extravasation accurately.Objective To compare the rates of cement leakage detected by intraoperative fluoroscopy, postoperative radiography, and postoperative computed tomography (CT) in a retrospective study.Patients and Methods The study included 78 patients (60 women and 18 men; 115 vertebral bodies) who were treated with two kinds of kyphoplasty. The patients underwent intraoperative fluoroscopy and postoperative radiography and CT. After surgery, the images were evaluated to compare cement leakage rates and locations in the three visualization techniques. Leakage locations were described as epidural, intradiskal, extravertebral, or intravascular.Results Compared with CT, intraoperative fluoroscopy regularly detected intradiskal leakage (75%) but had a considerably lower sensitivity for visualizing epidural (21%), extravertebral (31%), and intravascular (51%) cement leakages. A comparison of radiography and CT showed that radiography had a high sensitivity for detecting intradiskal (82%) and intravascular (70%) cement extrusions but a lower sensitivity in identifying epidural (42%) and extravertebral (50%) leaks. Therefore, the CT scan overall was best in detecting location and accuracy.Conclusion CT detected more cement leaks than any of the other investigated techniques, especially epidural, extravertebral, and intravascular cement leakages. To achieve the best accuracy, only CT provides complete information.
Keywords: kyphoplasty; radiography; computed tomography; cement leakage; fluoroscopy